2016
DOI: 10.1038/srep27326
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-mediated inflammatory response decreases mycobacterial survival in mouse MSCs by augmenting NO production

Abstract: Mycobacterium tuberculosis (MTB) is a hard-to-eradicate intracellular microbe, which escapes host immune attack during latent infection. Recent studies reveal that mesenchymal stem cells (MSCs) provide a protective niche for MTB to maintain latency. However, the regulation of mycobacterial residency in MSCs in the infectious microenvironment remains largely unknown. Here, we found that macrophage-mediated inflammatory response during MTB infection facilitated the clearance of bacilli residing in mouse MSCs. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Moreover, CD271 + bone marrow mesenchymal stem cells harboring MTB are localized in the hypoxic niche in both mice and humans, a critical microenvironmental factor that is known to induce dormancy [74]. The ability of mesenchymal stem cells to maintain MTB depends on the inflammatory milieu: Yang et al [75] reported that murine macrophages produced cytokines during mycobacterial infection that promoted clearance of MTB from mesenchymal stem cells by increasing production of nitric oxide in an IL-1β-dependent manner.…”
Section: Other Intracellular Nichesmentioning
confidence: 99%
“…Moreover, CD271 + bone marrow mesenchymal stem cells harboring MTB are localized in the hypoxic niche in both mice and humans, a critical microenvironmental factor that is known to induce dormancy [74]. The ability of mesenchymal stem cells to maintain MTB depends on the inflammatory milieu: Yang et al [75] reported that murine macrophages produced cytokines during mycobacterial infection that promoted clearance of MTB from mesenchymal stem cells by increasing production of nitric oxide in an IL-1β-dependent manner.…”
Section: Other Intracellular Nichesmentioning
confidence: 99%
“…It has been well noted that macrophages are the host primary cells, macrophage can destroy mycobacteria or be a reservoir for intracellular non‐tuberculous mycobacteria replication . In general, to fight against non‐tuberculous mycobacteria infection, macrophage can initiate innate immunity though recognition of pathogen‐associated molecular patterns (PAMP) by pattern‐recognition receptors (PRRs), such as activation of phagocytic pathway, production of nitric oxide (NO) and antibacterial peptide, release of pro‐inflammatory cytokines and chemokines, which was conceptually introduced as classical activation of macrophage, also termed as M1 polarization . Following the acute inflammatory burst, however, macrophages can remove cell debris and apoptotic inflammatory cells by so‐called efferocytosis and polarize into alternatively activated, M2 macrophages …”
Section: Introductionmentioning
confidence: 99%
“…NOS2 is not expressed in resting cells [ 13 ] and thus NOS2 is not active in HSCs. NOS2 is induced by inflammatory cytokines in MSCs and controls growth of intracellular M. tuberculosis in vitro [ 14 ] and, similarly, could also be induced in more mature hematopoietic progenitors to kill intracellular M. tuberculosis , as they develop from HSC. Thus, wild-type bone marrow would retain M. tuberculosis only in the resting LT-HSC, as we have seen previously in M. tuberculosis -infected wild-type bone marrow cells [ 5 ].…”
Section: Discussionmentioning
confidence: 99%